Self-assembly of Russian doll concentric porphyrin nanorings - Rousseaux, S; Gong, J; Haver, R; Odell, B; Claridge, T; Herz, L; Anderson, H (American Chemical Society, 2015)
Electronic communication between concentric macrocycles with wave functions that extend around their circumferences can lead to remarkable behavior, as illustrated by multiwalled carbon nanotubes and photosynthetic chlorophyll arrays. However, it is difficult to hold one π-conjugated molecular ring inside another. Here, we show that ring-in-ring complexes, consisting of a 6-porphyrin ring locked inside a 12-porphyrin ring, can be assembled by placing different metals in the two rings (zinc and aluminum). A bridging ligand with carboxylate and imidazole binding sites forms spokes between the two rings, resulting in a highly cooperative supramolecular self-assembly process. Excitation is transferred from the inner 6-ring to the outer 12-ring of this Russian doll complex within 40 ps. These complexes lead to a form of template-directed synthesis in which one nanoring promotes formation of a larger concentric homologous ring; here, the effective template is an eight-component noncovalent assembly. Russian doll templating provides a new approach to amplifying the size of a covalent nanostructure.